Pemberdayaan Remaja Puteri Sebagai Agent Of Change Pencegahan Kanker Serviks Di SMAN 7 Kota Bengkulu - Diniarti, Fiya; Bando, Epina Felizita (Jurnal Dehasen Mengabdi, 2025)
One of the leading causes of death in women in Indonesia is cervical cancer, which is generally caused by Human Papilloma Virus (HPV) infection. Education, vaccination, and early detection are effective prevention methods to increase public knowledge, especially for adolescent girls. In this article, we discuss a community service program that aims to encourage adolescent girls at SMAN 7 Bengkulu City to become agents of change in cervical cancer prevention. The program was implemented through seminars, health awareness campaigns, change agent training, and monitoring and evaluation. The results of the program showed an increase in adolescent girls' knowledge about cervical cancer. The lowest pretest score for students was 35 and the highest score was 89, while after cervical cancer prevention training, the lowest score was 65 and the highest score was 100, indicating that the training program provided to adolescent girls can increase knowledge about cervical cancer quite effectively. Adolescent girls as agents of change also succeeded in disseminating information to peers, families, and communities.This program shows that empowering young women as agents of change is an effective way to raise awareness and prevent cervical cancer. It is hoped that the young generation of Indonesia will be at the forefront of building a society that is aware of the importance of reproductive health.